2004
DOI: 10.1068/a36240
|View full text |Cite
|
Sign up to set email alerts
|

Gentrification and the Nature of Work: Exploring the Links in Williamsburg, Brooklyn

Abstract: This paper looks at the linkages between gentrification and the displacement of small-scale manufacturing and blue-collar work in the Williamsburg neighborhood of Brooklyn, New York. Although the link between global economic change and gentrification has been made for the upper classes who are the consumers of the gentrified landscape, very little work has been done on the bluecollar work and workers that remain in the central city despite the assumption by policymakers that deindustrialization is complete. I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 19 publications
(17 reference statements)
2
69
0
1
Order By: Relevance
“…Since Bell's 1973 book on the postindustrial society [63], many urban geographers have examined the land use conflict between industrial and non-industrial uses through a lens of gentrification beginning with Ley [64,65]. More recently, Curran [66][67][68][69] has published a series of qualitative studies on the displacement of small manufacturers via gentrification in the New York neighbourhoods of Greenpoint and Williamsburg. Other qualitative case studies on gentrification have covered the major Northwest cities of Portland [55], Vancouver, BC [48], and Victoria, BC [49].…”
Section: Environmental Inequities and Gentrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Bell's 1973 book on the postindustrial society [63], many urban geographers have examined the land use conflict between industrial and non-industrial uses through a lens of gentrification beginning with Ley [64,65]. More recently, Curran [66][67][68][69] has published a series of qualitative studies on the displacement of small manufacturers via gentrification in the New York neighbourhoods of Greenpoint and Williamsburg. Other qualitative case studies on gentrification have covered the major Northwest cities of Portland [55], Vancouver, BC [48], and Victoria, BC [49].…”
Section: Environmental Inequities and Gentrificationmentioning
confidence: 99%
“…Gentrification did not follow pollution cleanups and deindustrialization in the BINMIC area. Instead, industrial displacement through gentrification [66][67][68][69] better describes the process driving the restructuring of urban land use on Seattle's Northside.…”
Section: Environmental Gentrification and The Post-industrial Citymentioning
confidence: 99%
“…Located on the North West tip of Brooklyn that juts out into New York's East River, Williamsburg was an ideal location for manufacturing in the late nineteenth and twentieth centuries [3]. The surplus of factory jobs attracted immigrants, predominantly from Italy and Eastern Europe, to the neighborhood's 'Northside'.…”
Section: Williamsburg Brooklynmentioning
confidence: 99%
“…Through the combined efforts of public policy, real estate developers, and retail entrepreneurs, Williamsburg is dangerously close to being an upper class enclave [1]. The case of retail and residential gentrification in Williamsburg has already been studied by several scholars [2][3][4]. I intend to fill a gap in this literature by studying how uses of public space reflect the tensions and goals of a gentrifying neighborhood.…”
Section: Introductionmentioning
confidence: 99%
“…Curran (2007) concurs with this in Williamsburg, where the wide range of businesses she interviewed told negative tales of their displacement, from being 'paid off ' by their landlord to allow for residential conversion, forced downsizing or closure, multiple displacements from one manufacturing area to another and 'indirect displacement' , whereby the displacement of other industrial businesses impacted negatively on their business, causing them to relocate or close down. Ultimately, she argues the loss of industry from Williamsburg is not only due to deindustrialization, but to real estate speculation for residential conversion, actively promoted by developers, city planners, policymakers, landlords and individual gentrifiers (Curran, 2004). In Clerkenwell (London), Hamnett and Whitelegg (2007) found that demand for lofts originated not with artists, but with developers who manufactured demand through sophisticated marketing of 'ex-industrial city-centre chic' (p. 113) following the collapse of the secondary office market in the early 1990s and a search for alternative, profitable uses for the space.…”
Section: Arguesmentioning
confidence: 99%